Fulminant myocarditis associated with human rhinovirus A66 infection: a case report - Han, Shuaibing; Liu, Jing; Feng, Ziheng; Mao, Yiyang; Gao, Hengmiao; Xie, Zhengde; Qian, Suyun; Xu, Lili (Frontiers in Pediatrics, 2024)
Background Human rhinoviruses (HRVs) are among the most common pathogens of upper respiratory infections, and they are responsible for the common cold. An increasing number of studies have shown that HRV is associated with more severe illness. However, HRV-associated fulminant myocarditis has rarely been reported. A previously healthy 8-year-old boy developed fever, fatigue, and vomiting for 3 days, with a subsequent exacerbation accompanied by confusion lasting for 9 hours. The day before admission, the patient presented with oliguria, confusion, and hypotension, and he was suspected of having myocarditis. The patient was transferred to our hospital for further diagnosis and treatment. On admission, rough and moist rales were detected, and the heart sounds were muffled, accompanied by an irregular heart rhythm and a gallop. An electrocardiogram (EKG) revealed a wide QRS complex, ST-segment depression, premature ventricular contractions, and complete right bundle branch block. Laboratory tests revealed that brain natriuretic peptide (BNP), N-terminal pro BNP (NT-pro BNP), and cardiac biomarkers, such as troponin I, creatinine kinase (CK), andcreatinine kinase-MB (CK-MB) were elevated. Additionally, echocardiography revealed an ejection fraction of approximately 28%. The child developed severe cardiac dysfunction and tissue hypoperfusion, and the cardiogenic shock could not be corrected despite active drug therapy. He had indications for ECMO implantation. A rarely reported rhinovirus, namely, A66, was detected in his bronchoalveolar lavage fluid and oropharyngeal swabs via metagenomic next-generation sequencing and a PCR assay. Bacterial culture of all the samples yielded negative results. This case presents a patient with severe human rhinovirus A66 infection, which is likely responsible for fulminant myocarditis. This report facilitates prompt diagnosis and treatment of fulminant myocarditis.Clinicians should consider rhinovirus as a possible pathogen of fulminant myocarditis, especially when patients present with symptoms or signs of heart involvement.